O-25 BACTERIAL INFECTION ENHANCES THROMBIN GENERATION IN PATIENTS WITH CIRRHOSIS - Marina Pamponet Motta (Annals of Hepatology, 2021)
Introduction and Aims: Current concept of coagulopathy in cirrhosis indicates that there is a rebalancing of hemostasis with plasma hypercoagulability. Bacterial infection can promotes releases of endothelial heparinoids. However, the effect of this condition on the thrombin generation is unknown. Our aim was to assess the effect of bacterial infection on thrombin generation in cirrhosis. Methods: 36 patients with cirrhosis and bacterial infection (infected group) were evaluated within 24 hours after start antibiotic and at least 5 days after infection resolution. 28 patients with decompensated cirrhosis and not infected (not infected group) were also enrolled and reevaluated, without any intervention between evaluation times. Primary endpoint was the effect of bacterial infection on thrombin generation (TG) parameter ETP with TM (ETP TM). TM is a protein C activator added to mimic in vivo conditions. ROTEM assays, INTEM and HEPTEM (heparinase modified), was performed to evaluate the endogenous heparinoids effect. Protein C (PC) and antithrombin (AT) assays were performed. All results were compared within each group between evaluation times. Results: ETP TM values in infected cirrhotics were significantly higher than after resolution of infection (from 1145.4 ± 360.7 nmol/L*min to 958.1 ± 254.8 nmol/L*min, p=0.005) - figure 1. A heparinoid effect was found only in infected cirrhotics, with CTINTEM duration significantly longer than CTHEPTEM (p=0.004). This effect disappeared after resolution of infection (p=0.75). PC and AT deficiencies were significantly more severe in infected patients (p<0,01). RNI/TP, aPTT was worsen at active infection (p<0.05). None of these parameters exhibited a significant difference between inclusion and revaluation times in not infected group. Conclusion: patients with cirrhosis exhibits significant higher amount of TG during bacterial infection and it is associated with reduction of PC and AT levels. Despite the endogenous heparinoid effect during infection in cirrhosis, plasma hypercoagulability is preserved and cannot be assessed by conventional coagulation tests.